2005
DOI: 10.1177/0002716205278422
|View full text |Cite
|
Sign up to set email alerts
|

Giving Voice to Latino Voters: A Field Experiment on the Effectiveness of a National Nonpartisan Mobilization Effort

Abstract: In this article, I present a summary of the findings of a randomized field experiment of 465,134 registered Latino voters, the largest such experiment on Latinos to date. The National Association of Latino Elected and Appointed Officials’s (NALEO’s) Voces del Pueblo voter mobilization effort in 2002 explored three alternative modes of communicating with voters: direct mail, robotic phone calls, and live phone calls from volunteers. Of the three, only live phone calls produced a statistically significant increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 9 publications
2
61
0
Order By: Relevance
“…Existing randomized experiments have provided relevant information on the effect of campaigning and voter mobilization on election outcomes. It has been shown that impersonal methods of voter turnout communication such as robotic calls (Green and Karlan, 2006;Ramírez, 2005;Shaw et al, 2012) and emails (Nickerson, 2006b;Stollwerk, 2006) are recurrently ineffective. 10 On the other hand, non-partisan face-to-face canvassing (Gerber and Green, 2000), and phone calls (Imai, 2005;Arceneaux, 2007;Nickerson, 2006a;and Arceneaux and Nickerson, 2006) are more effective than non-personalized methods such as flyers.…”
Section: Why Might the Delivery Methods Matter?mentioning
confidence: 99%
“…Existing randomized experiments have provided relevant information on the effect of campaigning and voter mobilization on election outcomes. It has been shown that impersonal methods of voter turnout communication such as robotic calls (Green and Karlan, 2006;Ramírez, 2005;Shaw et al, 2012) and emails (Nickerson, 2006b;Stollwerk, 2006) are recurrently ineffective. 10 On the other hand, non-partisan face-to-face canvassing (Gerber and Green, 2000), and phone calls (Imai, 2005;Arceneaux, 2007;Nickerson, 2006a;and Arceneaux and Nickerson, 2006) are more effective than non-personalized methods such as flyers.…”
Section: Why Might the Delivery Methods Matter?mentioning
confidence: 99%
“…The empirical literature on the topic is remarkably thin. A recent contribution related to this line of inquiry finds suggests targeted, follow-up phone calls to committed voters increases the effectiveness of phone-bank campaigns (Michelson et al 2009), but greater scholarly attention has been devoted to investigating frequency effects (see Green and Gerber 2008 for a discussion about frequency of direct mail contacts and voter turnout) or the cumulative impact of combined treatments (Ramirez 2005). One recent study (Nickerson 2007) recognizes this void in the literature and seeks to test whether timing influences the effectiveness of GOTV phone calls delivered by a professional phone bank instructed to engage potential voters in a conversational way.…”
Section: Extant Scholarship On Message Timing Phone Calls and Mobilimentioning
confidence: 99%
“…Most experimental studies find little or no impact on participation as a result of such getout-the-vote phone drives (Gerber and Green 2005;Green and Gerber 2008;Cardy 2005;Panagopoulos 2009), although experimental evidence suggests nonpartisan phone appeals delivered by volunteers do raise participation by 3 to 5 percentage points (Nickerson et al 2006;Nickerson 2004;Ramirez 2005;Wong 2005). Nickerson (2007) suggests it is the quality of message delivery that matters most; the author finds that calls made by professional phone banks that engage voters in conversational ways (i.e., ''high-quality'' calls) can effectively mobilize, while hurried volunteer calls (''standard'') exert no impact.…”
Section: Extant Scholarship On Message Timing Phone Calls and Mobilimentioning
confidence: 99%
“…The use of field experimentation to test for the effects of mobilization has increased over the last five years, with scholars studying many different types of direct contact strategies. Overall, studies show small and mixed effects for mailers, phone calls, and e-mails on increasing the likelihood of turnout (Gerber and Green, 2000;Gerber, Green, and Green, 2003;McNulty, 2005;Nickerson et al, 2006;Ramirez, 2005;Wong, 2005). The most promising form of direct contact seems to be door-to-door canvassing, which has a stronger effect on increasing the likelihood of turnout compared to other methods such as phone banks and mailings, regardless of whether the contact is non-partisan or partisan (Gerber and Green, 2000;Nickerson, Friedrich, and King, 2006).…”
Section: Direct Mobilization Effectsmentioning
confidence: 99%